The economics of Alfred Marshall - Reisman, David (Taylor and Francis, 2013)
First published in 1986, The Economics of Alfred Marshall is concerned with the theories of demand, supply, market structure and income distribution which the celebrated author of the Principles of Economics developed while standing on the shoulders of giants. It is thus concerned with hidden assumptions, institutional constraints, tentative conclusions and blurred distinctions; for these are an integral part of the contribution of an economist who warned against spurious over-simplification of that which is inherently complex. The economics of Alfred Marshall appear.
Keywords: Marshall, Alfred -- 1842-1924; Neoclassical school of economics.; École néoclassique d'économie politique.; BUSINESS & ECONOMICS -- Economics -- General.; BUSINESS & ECONOMICS -- Reference.; Neoclassical school of economics; Wirtschaftstheorie; Neoklassische Theorie; Electronic book.